2021
DOI: 10.3389/fphar.2021.667874
|View full text |Cite
|
Sign up to set email alerts
|

Repurposing of Anti-Diabetic Agents as a New Opportunity to Alleviate Cognitive Impairment in Neurodegenerative and Neuropsychiatric Disorders

Abstract: Cognitive impairment is a shared abnormality between type 2 diabetes mellitus (T2DM) and many neurodegenerative and neuropsychiatric disorders, such as Alzheimer’s disease (AD) and schizophrenia. Emerging evidence suggests that brain insulin resistance plays a significant role in cognitive deficits, which provides the possibility of anti-diabetic agents repositioning to alleviate cognitive deficits. Both preclinical and clinical studies have evaluated the potential cognitive enhancement effects of anti-diabeti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 181 publications
(206 reference statements)
2
15
0
Order By: Relevance
“…On the contrary, treatment with metformin was associated with a significant increase in BDNF when compared with the D-gal group. Our results were in agreement with previously published reports which demonstrated that metformin up-regulates BDNF via AMPK activation 47 .…”
Section: Discussionsupporting
confidence: 94%
“…On the contrary, treatment with metformin was associated with a significant increase in BDNF when compared with the D-gal group. Our results were in agreement with previously published reports which demonstrated that metformin up-regulates BDNF via AMPK activation 47 .…”
Section: Discussionsupporting
confidence: 94%
“…5 Newer GLDs have generated significant interest in their neuroprotective effects by improving insulin resistance and reducing oxidative damage and inflammation, which make them promising therapeutic options for the management of PD. 6 The results of this study indicated a potential benefit of SGLT2 inhibitors in reducing the risk of PD, which aligns with previous research findings. 36,37 A recently published population-based cohort study involving people with T2D found a significant association between SGLT2 inhibitors and a lower risk of PD compared to DPP-4 inhibitors (hazard ratio [HR]: 0.28; 95% CI: 0.09-0.91).…”
Section: Discussionsupporting
confidence: 91%
“…First, because this study was designed to be cross‐sectional, we collected data at a single point in time and, therefore, could not determine the causality of cognitive impairment related to prediabetes. Second, although some anti‐diabetic drugs, particularly metformin and glucagon‐like peptide‐1 receptor agonists, may have beneficial effects on cognitive function in PD patients (Chen et al., 2021 ), we could not access each patient's medications in the diabetes group due to lack of data. Thus, the effect of diabetes on cognition in our dataset may have been underestimated.…”
Section: Discussionmentioning
confidence: 99%